Effect of acute caffeine ingestion on EPOC after intense resistance training - Astorino, T. A.; Martin, B. J.; Wong, K.; Schachtsiek, L. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: This study investigated the effect of acute caffeine (CAF) intake on postexercise oxygen consumption (EPOC) after intense resistance training. METHODS: Fourteen strength-trained men (mean±SD age and mass =23.1±4.2 yr and 83.4±13.2 kg, respectively) who were caffeine users initially completed one-repetition maximum testing (1-RM) of four exercises: bench press, leg press, lat row, and shoulder press. On each of two days separated by one week, they completed four sets of each exercise to fatigue at 70-80% 1-RM, which was preceded by ingestion of CAF (6 mg/kg) or placebo. Pre-exercise, indirect calorimetry was used to assess energy expenditure for 35 min; this was repeated for 75 min postexercise while subjects remained seated in a quiet lab. Two-way analysis of variance with repeated measures was used to examine differences in gas exchange variables across time and treatment. RESULTS: Results revealed that EPOC was significantly higher (P<0.05) with CAF (26.7±4.1 L) compared to placebo (22.8±3.8 L). With CAF ingestion, oxygen uptake was significantly higher (P<0.05) from 10 min pre-exercise to 70 min postexercise. Respiratory exchange ratio was significantly different (P<0.05) with CAF versus placebo. Caffeine intake increased total energy expenditure by 15% (P<0.05), but the additional calories burned was minimal (+27 kcal). CONCLUSION: Caffeine ingestion in individuals regularly completing rigorous resistance training significantly increases EPOC and energy expenditure pre-and post-exercise, yet the magnitude of this effect is relatively small.